Can Contrast‐Enhanced Sonography Detect Bowel Wall Fibrosis in Mixed Inflammatory and Fibrotic Crohn Disease Lesions in an Animal Model?. (10th January 2017) - Dillman, Jonathan R.; Rubin, Jonathan M.; Johnson, Laura A.; Moons, David S.; Higgins, Peter D. R.
Abstract : Objectives: To determine whether contrast‐enhanced sonographic quantitative perfusion parameters can detect bowel wall fibrosis in the setting of mixed inflammatory and fibrotic lesions in a Crohn disease animal model. Methods: This study was approved by the institutional Committee on the Use and Care of Animals. Multiple (range, 1–5) 2, 4, 6‐trinitrobenzenesulfonic acid–ethanol enemas were used to create intestinal inflammatory lesions with variable fibrosis in female Lewis rats. Low–mechanical index contrast‐enhanced sonography was performed 3 days after the final enema using a 0.2‐mL bolus of sulfur hexafluoride microbubbles injected through a tail vein. Contrast‐enhanced sonographic data were analyzed with software that converts video data into echo‐power (linearized) data. Colorectal lesions were scored for histopathologic inflammation and fibrosis; bowel wall collagen was quantified by Western blotting. The Spearman correlation was used to assess associations between contrast‐enhanced sonographic quantitative parameters and bowel wall collagen; the Kruskal‐Wallis test was used to compare continuous results between histopathologic groups. Results: Thirty‐one animals were included in our analysis. Animals were placed into 3 histopathologic cohorts: (1) severe bowel wall inflammation/minimal or no fibrosis (n = 11); (2) severe bowel wall inflammation/moderate fibrosis (n = 9); and (3) severe bowel wall inflammation/severe fibrosis (n = 11). Western blotting showed a significant difference in bowel wall collagen between histopathologic cohorts ( P  = .0001). There was no correlation between any contrast‐enhanced sonographic quantitative parameter and bowel wall collagen ( P  > .05). There was no difference between histopathologic cohorts for any contrast‐enhanced sonographic quantitative parameter ( P  > .05). Conclusions: Contrast‐enhanced sonographic quantitative perfusion parameters failed to effectively detect bowel wall fibrosis in the setting of superimposed inflammation in a Crohn disease animal model.